Impact of Generative AI Technologies on Software Development Professionals' Perceptions of Job Security - Malheiros, Phelipe Silva; Lima, Rayfran Rocha; Oran, Ana Carolina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
CONTEXT: The rapid evolution of generative AI technologies has sparked significant interest in the software development sector. These technologies promise to automate repetitive tasks, improve code quality, and assist in various managerial and technical activities. Despite the advancements and benefits of AI tools, there are concerns about how these technologies might impact job security for software development professionals. The main question is whether these professionals feel threatened by the possibility of being replaced by AI tools. OBJECTIVE: This study aims to investigate the impact of generative AI technologies on software development professionals, particularly focusing on their perceptions of job security. The research seeks to determine whether these professionals feel threatened by AI technologies and what their expectations are for the future. METHOD: An opinion survey was conducted with professionals in the software development field. The questionnaire, divided into sections on personal characteristics, AI usage, perceptions of job impact, confidence, and recommendation, was distributed online and analyzed using quantitative and qualitative methods. RESULTS: The survey revealed evidence that the majority of professionals do not currently feel threatened by AI tools, but there is uncertainty about the future, especially in the long term. The study also highlighted the main benefits of AI tools in reducing time spent on coding and improving documentation quality. However, challenges such as clarity in communication with AI and technical limitations were also noted. CONCLUSION: Generative AI technologies are seen as complementary to human work, enhancing the efficiency and quality of software development. However, the uncertainty about long-term job security suggests the need for balanced strategies to integrate these technologies in a way that maximizes benefits while minimizing risks.